An Uneven Landscape: A Review of Cabezón’s Sexuality in Classical South Asian Buddhism - Collett, Alice (The journal of religion, 2021)
José Ignacio Cabezón’s Sexuality in Classical South Asian Buddhism is a book that caught people’s attention as soon as it was released. The book is, essentially, a work that concentrates on an analysis and assessment of views on sex, sexuality, and sexual deviance within South Asian Buddhist traditions. It is also marketed as a book on gender. While sections on gender do form part of the book (by necessity), this is less of a focus than the marketing suggests. I title my review "An Uneven Landscape" because while the core of the book, on sexuality, is a milestone in scholarship on this underresearched topic, Cabezón’s analysis of women and gender leaves much to be desired. I focus in this review article on the problems with the volume, while not seeking to devalue the core of the book. Nonetheless, the issues are, to my mind, considerable.